A contrastive study of some English and Ilocano intonation patterns an introduction - Camacho, Socorro Nacionales 1935- ([Quezon City College of Education, University of the Philippines Diliman], 1964)
The objectives of this paper are: (1) to attempt a comparison between English and Ilocano intonation and (2) to predict learning difficulties or problems based on this study.
Thesis (Master of Arts in Teaching (English))--University of the Philippines Diliman.
Keywords: English language -- Intonation; Iloko language -- Intonation